Dampak Intensitas Cahaya Terhadap Kelelahan Mata Pada Karyawan di Ruang Staff Kantor PT (X) di Palembang Tahun 2024 - Fikri, Haslam; Hariani, Yuli; Triana, Neni (JURNAL KESEHATAN TERAPAN, 2024)
Eye fatigue is the result that occurs Eye fatigue occurs eyes and is caused by using the sense sight at work and requires the ability to see objects for long periods of time, usually accompanied by the eyes being in an uncomfortable viewing condition. The objective of this study is to establish relationship between age, length of service and length of work with fatigue among PT (X) Palembang office staff workers. The entire population and the selected sample for this study consisted of workers or office staff at PT (X) Palembang, numbering 20 workers. Samples were taken using In the study conducted at PT (X) in 2024, total sampling was used alongside Fisher's Exact Test as the statistical method. The findings indicated significant relationships between several factors and eye fatigue: age p = 0.004, work experience p = 0.019, duration of employment p= 0.004, and light intensity p = 0.001 among office staff. Therefore, the study concludes that age, work experience, length of work, and light intensity are associated with eye fatigue in this population. Suggestion: If employees still experience complaints of eye fatigue such as red eyes, stinging, headaches, etc., employees should relax or rest their eyes.